Retroiliac ureter with persisting mesonephric duct and vesicoureteral reflux presenting as left inguinal mass during defecation: a case report - Yijun Zhao; Linfeng Zhu; Fan Yang; Guangjie Chen (BMC Urology)
Abstract Background Retroiliac ureter is an extremely rare congenital anomaly, even more rarely accompanied by persisting mesonephric duct and vesicoureteral reflux(VUR). We report such a unique case involving a left inguinal mass that appeared during defecation. Case presentation A two-year-old boy presented with a tubular structure resembling a dilated ureter discovered incidentally during open left inguinal hernia repair. Contrast radiography and voiding cystourethrogram(VCUG) revealed a tubular structure in the left groin mimicking a ureter, with grade IV reflux into a branch-shaped left renal pelvis. Three-dimensional CT reconstruction demonstrated a dilated left ureter and a tubular structure distortion, angulation, and depression at the L5–S1 level. Cystoscopy showed the left ureteral orifice near the midline of bladder trigone. Laparoscopic exploration revealed an abnormally deep aortic bifurcation in the left iliac fossa, superior to the left ureter and the tubular structure. The left vas deferens was absent, while the tubular structure traversed the internal ring with the left spermatic vessels and inserted into the distal ipsilateral ureter. Four years later, the patient was readmitted due to decreased left renal function. VCUG persistent left-sided grade IV VUR. Robot-assisted laparoscopic left ureter reimplantation via the Lich-Gregoir technique was conducted, along with resection of the abdominal and inguinal segment of the dilated tubular structure and closure of the ipsilateral internal ring. The tubular structure was ultimately confirmed as an abnormally dilated left vas deferens, and the diagnosis of retroiliac ureter accompanied by persisting mesonephric duct and VUR was made. At the 3-month follow-up, ultrasonography revealed mild hydronephrosis and ureteral dilation of left kidney. Conclusion Diagnosing retroiliac ureter with persisting mesonephric duct and VUR is challenging. Although imaging provide critical information, surgical exploration is often required for definitive diagnosis. Treatment involves vas deferens excision and ureteral reimplantation to preserve renal function.